PENINGKATAN HASIL BELAJAR DAN DISPOSISI MATEMATIS SISWA DALAM MENYELESAIKAN SOAL CERITA BARISAN DAN DERET MELALUI MODEL PEMBELAJARAN LAPS HEURISTIK BERBANTUAN APLIKASI WHATSAPP - Rika Nur Safitri; Ali Shodikin; Arezqi Tunggal Asmana (INSPIRAMATIKA, 2020)
This study aims to determine the increase in learning outcomes of student’s mathematical disposition in solving story sequence and sequence problem through the learning model LAPS Heuristic assisted by Whatsapp messenger. this type of research is an esperiment with a quantitative approach. Data collection method is done by the method of test and questionnaire. The study was conducted by giving 4 items of pretest and posttest regarding the settlement of row and series problems and a mathematical disposition questionnaire at the beginning and end of the study. The data analysis echnique used is the normaity test, the homogeneity test and the average difference test. Theresult of the study indicate: (1) there are differences in the achievement of learning outcomes and student’s mathematical disposition in solving story sequence questions and sequencesthrough learning LAPS Heuristic of Whatsapp assisted with conventional learning; (2) there is a difference in the improvement of learning outcomes and the mathematical disposition of students in solving story sequence questions and sequence through the learning model assisted by the whatsapp application.